Designing a field experience tracking system in the area of special education. Issue 5 (28th October 2014) - He, Wu; Watson, Silvana
Abstract : Purpose: – To improve the quality of field experience, support field experience cooperation and streamline field experience management, the purpose of this paper is to describe the experience in using Activity Theory to design and develop a web-based field experience tracking system for a special education program. Design/methodology/approach: – The authors used Activity Theory to design and develop a web-based field experience tracking system for a special education program. An in-depth evaluation of the developed web-based system including usability testing and actual use of the system was conducted. Findings: – The evaluation and data analysis results demonstrate the value of Activity Theory and show that a web-based tracking system is a valuable tool to support the management of pre-service teachers' field experiences. Originality/value: – This is the first paper to discuss the design and development of field experience tracking system using Activity Theory. This paper can be used to motivate other developers to use Activity theory to design campus-wide information system. The system and methodology the authors used in this project has wider applicability and generalizability, and can be applied to the management of other competency and field based professional training in areas such as nursing, social work and medicine.